Multilateral trade agreements as a basis for foreign economic cooperation by the example of EU countries - KENZHIN, Zhaxat; KAMALI, Karlygash; KARGABAYEVA, Saule; ZAMANBEKOVA, Altynshash; YERNIYAZOVA, Zhanat (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of multilateral trade agreements on the gross domestic product (GDP) of EU countries in the context of foreign economic cooperation. The objective is to assess whether the number of such agreements correlates with GDP levels while considering related factors. The analysis applies the Pareto principle to classify EU countries into two groups based on GDP volume. It reveals that both groups display similar levels of economic freedom (69–72%), while countries with higher GDP and lower tax revenues report a greater number of trademark applications from foreign companies. Correlation analysis identifies a strong dependence of GDP on exports, imports, and economic freedom, with correlation coefficients exceeding 90%. These factors are thus considered key drivers of GDP growth. A regression model (R² = 0.862) confirms a significant positive relationship between the number of multilateral trade agreements and changes in export volumes. The findings suggest that such agreements are instrumental in shaping economic policies and fostering integration within the EU. The study underscores the practical relevance of these results for policymaking, particularly in designing strategies aimed at enhancing national competitiveness and promoting sustainable economic growth across the region.